A Case Report of Extensive Pyoderma Gangrenosum on the Upper Third of the Body - Gunawan H; Maharani RH; Achdiat PA; Hindritiani R (Dove Medical Press, 2021)
Hendra Gunawan, Retno Hesty Maharani, Pati Aji Achdiat, Reti Hindritiani Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Bandung, IndonesiaCorrespondence: Hendra GunawanDepartment of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Jl. Pasteur No. 38, Bandung, West Java, 40161, IndonesiaTel +62 222032426 ext. 3449Fax +62 222032426Email h.gunawan2016@unpad.ac.idAbstract: Pyoderma gangrenosum (PG) is a sterile inflammatory neutrophilic dermatosis that can present as a peristomal, pustular, bullous, vegetative, or ulcerative variant. It commonly affects the lower extremities, mainly in the pretibial area. We describe a case of extensive PG in an 18-year-old Indonesian man, involving the upper third of the body. Dermatological examination showed multiple painful ulcers with violaceous borders on the face, occipital region of scalp, neck, shoulder, upper chest, and back. The diagnosis of PG was established based on the histopathological examination that revealed massive dermal neutrophilic infiltration mixed with lymphocytic inflammatory infiltrates accompanied by leukocytoclastic vasculitis. The patient was treated with methylprednisolone equivalent to 1 mg/kg/day of prednisone. An excellent response to therapy also confirmed the diagnosis of PG. Since lesions of PG can appear on any part of the body, including the upper third of the body, a complete and appropriate examination is useful in establishing diagnosis.Keywords: extensive, pyoderma gangrenosum, upper third of the body